Rancang Bangun Turbin Angin Sumbu Horizontal Pada Kecepatan Angin Rendah Untuk Meningkatkan Performa Permanent Magnet Generator - Teuku Multazam; Andi Mulkan (Jurnal Serambi Engineering, 2019)
Wind power is dominant energy converted into electricity through wind turbine generators used in wind energy conversion systems. Technological developments produce various types of generators for use in wind power plants of various scales. Permanent magnet generator (PMG) has advantage of being able to produce electrical energy of 500 watts at rotation 600 rotate per minute with an input wind speed of 2.5-12 m/s. The potential for average wind speed throughout the year in Aceh is around 1.5-6.5 m/s cannot be generate electric power because mechanical energy from turbine rotation is not sufficient to meet the minimum demand for RPM generators. The design of a horizontal axis wind turbine (HAWT) with Air Foil Naca 2410 is used to increase the efficiency of the turbine rotation. It’s influenced by variations in the number of blades and material used. Stages of simulation are prioritized to get efficient variations of the number of blades and the most effective material testing is performed. The results showed that variation of the axis of a three-blade wind turbine type has a higher coefficient of power that is 50 percent compared the other, the type of material wind turbines made from pinus more optimal than fiberglass.